Application of the innovative methods of mathematical modeling in the development of standards for providing the ambulatory link by doctors in Russia - N. E. Guryanova; M. A. Ivanova; L. A. Soprun (Biomedical Photonics)
The work presents data on the relationship between the regional incidence of gastrointestinal tract diseases and the number of medical personnel in various regions of the Russian Federation. Indicators for all federal districts for 2013-2017 have been studied. Mathematical models describing this relationship have been proposed. It has been shown that regional morbidity correlates with the number of medical personnel, as well as with attendance at treatment and prevention institutions. The average number of gastroenterologists from 1.3 to 1.5 per 100,000 inhabitants of the region is optimal for the timely detection of gastroenterology diseases. The data obtained can be used in management decisions to optimize the burden on the healthcare system in each region. The introduction of the standards into clinical practice under the established procedure will help to improve the quality of specialized care for patients with gastroenterological problems.